6. BUDGET IMPACT ANALYSIS OF CARDIOVASCULAR DISEASES: A STUDY AT LE VAN THINH HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to analyze the budget impact of treating cardiovascular diseases at Le Van Thinh Hospital (LVT Hospital) from 2018 to 2023.Subjects and methods: A cross-sectional descriptive study was conducted through a retrospective review of data related to cardiovascular disease treatments at LVT Hospital during the 2018-2023 period. The budget impact was analyzed through the total healthcare costs covered by health insurance each year, categorized by disease groups, inpatient/outpatient treatments, and cost components. Data were processed and compiled using Excel, and analyzed with R software.Results: From 2018 to 2023, health insurance covered 85.0% of the total treatment costs for 746,159 treatment visits for cardiovascular diseases at LVT Hospital. Outpatient treatments accounted for 85.2% of the costs for 735,194 visits, while inpatient treatments accounted for 14.8% of the costs for 10,965 visits. Across the entire hospital, 81.2% of the costs were concentrated on treating hypertension, predominantly on outpatient care. In inpatient treatment, nearly 50% of the costs were equally divided between cerebrovascular diseases (25.1%) and hypertension (21.9%). The average cost per outpatient cardiovascular treatment visit increased over time (from VND 399,900 per visit in 2018 to VND 572,000 per visit in 2023). Medications accounted for 74.9% of the total treatment costs across the hospital. Laboratory and imaging costs were divided in a 2:1 ratio between outpatient and inpatient treatments, respectively.Conclusion: The information provided by this study will help hospital management comprehensively assess the use of hospital financial resources in treating cardiovascular diseases, thereby facilitating necessary interventions to optimize treatment costs.
Keywords: Budget impact, health insurance, direct medical costs, hypertension, cardiovascular diseases, Le Van Thinh Hospital